Penggunaan Teknologi Dalam Proses Peradilan Serta Dampaknya Terhadap Akses Keadilan (Acces To Justice) - Taufiqurrohman Syahuri; M. Reza Saputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Technological developments ultimately require judicial bodies in various countries, including Indonesia to adopt the use of technology. Because the administration of Indonesian justice is based on the principle of simple, fast, and low cost. Utilization of information technology in the judicial process can increase the effectiveness and efficiency of the performance of the judiciary, so that it can answer the public's sense of justice. Because the main problems that are often faced in our judiciary are the slow handling of cases, the difficulty of accessing cases and the integrity of the judicial administration apparatus. This article is intended to examine how to regulate the use of technology in the judiciary, and how it impacts on access to justice. This article concludes, Electronic court proceedings need to be regulated in the law itself or accommodated in the current procedural law. Because the mission of adaptation and harmonization of various legal developments is very necessary. In addition, the government must also pay more attention to the readiness of courts in Indonesia to carry out using technology. For example, providing direction for building or upgrading electronic facilities for trials, both in courts and correctional facilities, as well as recruiting and providing IT human resources. So that by using technology can run effectively and efficiently.